Students’ Perspective about E-Learning Problems and its Benefits - Nia, Nur Jazilah; Kurniawan, Fachrul (Letters in Information Technology Education (LITE), 2019)
Current technological developments force prospective educators to follow and even exploit its development to support the instructor and students. Besides that, we cannot simply move on with its rapid development now. E-Learning is one of the breakthroughs in the field of education that is allegedly able to improve the quality and quality of students in learning. For that prospective educators must also understand what E-Learning is. The purpose of this research is to determine the level of understanding of students majoring in education at UIN MALIKI Malang about E-Learning and its utilization for students. In order to make adjustments to the education curriculum at the PTN level related to the issue of E-Learning itself. The author will conduct interviews indirectly with interviewees to ask about E-Learning problems and its benefits. After conducting research it shows that 54.1% of students have not fully understood about this issues.